Deep-sea Bodotriidae, Diastylidae and Pseudocumatidae (Cumacea, Crustacea) from the southeastern Atlantic - Mühlenhardt-Siegel, Ute (Zootaxa, 2014)
Nine species of the family Diastylidae, two species of the family Bodotriidae and one species of the family Pseudocumatidae are present in the Diva II and Ifremer collections. Two new species were recognized and described herein. However, one of the new species has to remain in open nomenclature due to its young developmental stage. The new species are Makrokylindrus (Makrokylindrus) abyssalis, and M. (Adiastylis) sp.1. The distribution range is enlarged based on the new findings for seven species.